PARTICIPATION OF EASTERN COUNTRIES IN THE SOVIET FAIR TRADE AND THE ISSUE OF ORGANIZING AN INTERNATIONAL FAIR IN CENTRAL ASIA (1920s) (Western European Journal of Historical Events and Social Science, 2025)
This article examines the participation of Eastern countries in Soviet trade fairs in the 1920s, the activities of Central Asian economic agencies in this issue, namely the organization of an international trade fair in the region, and the position of central foreign trade organizations regarding it, based on historical materials of that period